2018
DOI: 10.1177/2051570718769201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the number of ingredient images on package evaluation and product choice

Abstract: In the highly competitive context of food product sales in supermarkets, consumers may have difficulty processing deeply the information on a given package. This research examines how the number of ingredients depicted on packaging in addition to the picture of the whole product impacts its efficacy depending on consumers’ motivation (hunger), opportunity (via cognitive load), and ability (via need for cognition – NFC) to process information. Three studies find that, under high cognitive load, packages depicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 85 publications
2
14
0
Order By: Relevance
“…Additionally, for the 3D packaging, adding an element of monitoring pictorial attention (i.e., eye tracking) could help in understanding and identifying these groups, as consumers tend to overestimate their label use when self-reporting [79]. Also, gaining knowledge in localization of attention could provide ways in which label design could be modified to improve consumers’ ability to locate and effectively utilize factual nutrition information such as the ingredient list [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for the 3D packaging, adding an element of monitoring pictorial attention (i.e., eye tracking) could help in understanding and identifying these groups, as consumers tend to overestimate their label use when self-reporting [79]. Also, gaining knowledge in localization of attention could provide ways in which label design could be modified to improve consumers’ ability to locate and effectively utilize factual nutrition information such as the ingredient list [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…It is a quasi‐pictorial representation that affects how information is processed (Dahl et al, 1999). Prior work has shown that images stimulate mental imagery by consumers since images allow consumers to “mentally picture” themselves using the product (McGill & Anand, 1989; Thomas & Capelli, 2018). We reason that larger food image sizes should induce greater mental imagery, compared to smaller image sizes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Prior studies have revealed that, under high cognitive load, packages depicting several ingredients (3-5) induce more purchase intent; whereas under low cognitive load, the consumers' purchase intent does not depend on the number of ingredients depicted (Thomas and Capelli, 2018). Thus, we set up restricted information about green products in each scenario, including health benefit, product quality, environmental impact and eco-certification.…”
Section: Manipulationmentioning
confidence: 99%